2020
DOI: 10.1001/jamapsychiatry.2019.4275
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Subjection to Violence and Perpetration of Violence in Persons With Psychiatric Disorders in Sweden

Abstract: IMPORTANCE Key outcomes for persons with psychiatric disorders include subjection to violence and perpetration of violence. The occurrence of these outcomes and their associations with psychiatric disorders need to be clarified. OBJECTIVE To estimate the associations of a wide range of psychiatric disorders with the risks of subjection to violence and perpetration of violence. DESIGN, SETTING, AND PARTICIPANTS A total of 250 419 individuals born between January 1, 1973, and December 31, 1993, were identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 45 publications
4
95
2
2
Order By: Relevance
“…The probability of any crime victimisation occurring within 5 years of an individual's first homeless shelter contact was 23% (95% CI 21-26) in females and 16% (15)(16)(17)(18) in males. These estimates were substantially higher than those in matched controls from the general population (10% [10][11] in females and 7% [7][8] in males 5 years after matching). Over the same time period, the probability of being the victim of a violent crime was 12% (10)(11)(12)(13)(14) in females and 11% (10)(11)(12) in males who had had contact with a homeless shelter (figure 2B; appendix p 5).…”
Section: Malesmentioning
confidence: 64%
See 1 more Smart Citation
“…The probability of any crime victimisation occurring within 5 years of an individual's first homeless shelter contact was 23% (95% CI 21-26) in females and 16% (15)(16)(17)(18) in males. These estimates were substantially higher than those in matched controls from the general population (10% [10][11] in females and 7% [7][8] in males 5 years after matching). Over the same time period, the probability of being the victim of a violent crime was 12% (10)(11)(12)(13)(14) in females and 11% (10)(11)(12) in males who had had contact with a homeless shelter (figure 2B; appendix p 5).…”
Section: Malesmentioning
confidence: 64%
“…1 Homeless individuals have complex health problems, including psychiatric disorders, 2,10 and both substance use disorders and mental illnesses are linked to increased risk of victimisation. 1,11,12 Lifetime victimisation rates have been suggested to be higher in homeless adults with severe mental illness than in their housed counterparts. 13 A systematic review of homeless youth reported an unclear association with sexual crime victimisation, and highlighted the need for future prospective studies and studies taking into account the situational context of homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…2 A 2016 systematic review of 30 studies found a strong association of severe mental illness with victimisation in both men and women, in comparison with the general population. 3 Large register-based epidemiological studies in the USA, 4 Sweden 5 and Denmark 6 confirm the association between mental disorders and subsequent experience of violent crime.…”
Section: Introductionmentioning
confidence: 91%
“…Violence is a global public health challenge [1]. While symptoms of mental disorders have long been understood to be a potential consequence of violent victimization, recent research indicates such symptoms might also increase vulnerability to later victimization [2,3]. However, much previous research has focused on mental disorders in help-seeking populations (e.g., Christ et al [4], reviewed in Khalifeh et al [5[), rather than symptoms of common mental disorders, such as depressed mood and suicidality, occurring in people who may not be seeking help.…”
Section: Introductionmentioning
confidence: 99%